Efficacy of oxamniquine and praziquantel in the treatment of Schistosoma mansoni infection: a controlled trial - Ferrari M.L.A; Coelho P.M.Z; Antunes C.M.F; Tavares C.A.P; Cunha A.S. da (The World Health Organization, 2003)
OBJECTIVE: To evaluate the therapeutic efficacy of oxamniquine and praziquantel, the two most clinically important schistosomicide drugs, and to compare the accuracy of faecal examination with the accuracy of oogram in testing for Schistosoma mansoni infection. METHODS: In a triple-masked and randomized controlled trial, 106 patients infected with S. mansoni were randomly allocated to one of three statistically homogeneous groups. One group was given 60 mg/kg praziquantel per day for three consecutive days, another was given two daily doses of 10 mg/kg oxamniquine, and the placebo group received starch. Faecal examinations (days 15, 30, 60, 90, 120, 150, and 180 after treatment) and biopsy of rectal mucosa by quantitative oogram (days 30, 60, 120, and 180) were used for the initial diagnosis and for evaluating the degree of cure. The chi2 test and the Kruskal-Wallis test were used to compare variables in the three groups. Survival analysis (Kaplan-Meier) and the log-rank test were used to evaluate the efficacy of the treatments. FINDINGS: The sensitivity of stool examinations ranged from 88.9% to 94.4% when patients presented with >5000 S. mansoni eggs per gram of tissue (oogram); when the number of eggs dropped to <1000 eggs per gram, sensitivity was reduced (range, 22.7-34.0%). When cure was evaluated by stool examination, oxamniquine and praziquantel had cure rates of 90.3% and 100%, respectively. However, when the oogram was used as an indicator of sensitivity, the oxamniquine cure rate dropped dramatically (to 42.4%), whereas the rate for praziquantel remained high, at 96.1%. CONCLUSIONS: Praziquantel was significantly more effective than oxamniquine in treating S. mansoni infection. The oogram was markedly more sensitive than stool examinations in detecting S. mansoni eggs and should be recommended for use in clinical trials with schistosomicides.